Transformational Leadership and Adaptive Human Resource Capability for Digital-Era Employee Job Satisfaction - Denny Aditya Dwiwarman (Jurnal Minfo Polgan, 2026)
The research motivation is the impact of digitalization on the working process in the public sector; thus, the workforce should demonstrate its responsibility and collaboration, accuracy, and flexibility in working processes. Research objectives aim to analyze the relationship between transformational leadership and adaptive competence of HR in community and village empowerment office of Cianjur regency based on the object of research, which is employees’ job satisfaction in terms of digitalization process within community and village empowerment office of Cianjur regency. To carry out the research, the researcher decided to use quantitative approach; meanwhile, the type of research is explanatory survey. Simple random sampling is applied when selecting samples from the target population; it included 30 respondents from the Community and Village Empowerment Office of Cianjur District. The research methodology includes validity tests, reliability test, classical assumption test, multiple regression analysis, coefficient of determination, t-tests and f-tests. The method of collecting the data is a questionnaire with 5-point Likert Scale. There is a positive correlation between Transformational Leadership and job satisfaction of the employees. (t-value=0). From the analysis above, the output reveals that the t-value is 4.501 while the significance level is <0.001, implying that there is a significant and positive influence of the transformational leadership towards job satisfaction of employees. Again, the adaptive human resource capacity has a very significant effect on the dependent variable with the t-value of 3.156 and significance level of 0.004. The two independent variables are positively affecting with the F value of 34.932 and F value of <0.001 respectively. Additionally, the coefficient of determination (R-squared) obtained is 0.721, implying that 72.1 percent of the total variance in job satisfaction of employees can be predicted by the model developed from this study. What makes the current research distinct from other similar studies is that the researcher managed to position the concept of adaptive human resource capacity as a strategic variable in order to explain job satisfaction among the employees in the public sector. The outcomes reveal the areas where improvements are necessary such as transformational leadership, digital learning, cross functional collaboration and change readiness. Future researchers need to adopt bigger sample size in addition to incorporating more organizations in the public sector and considering mediating and moderating variables.